Spin-Coating Process for 10 cm x 10 cm Perovskite Solar Modules Enabled by Self-Assembly of SnO2 Nanocolloids - Han, Gill Sang; Kim, Jio; Bae, Seunghwan; Han, Sehoon; Kim, Yong Joo; Gong, Oh Yeong; Lee, Phillip; Ko, Min Jae; Jung, Hyun Suk (AMER CHEMICAL SOC, 2019)
Recently, scalable perovskite fabrication techniques for large, uniform, and highly crystalline perovskite layers have been developed by controlling the crystal chemistry of perovskite precursors. However, scalable techniques for the electron and hole transport layers (ETL and HTL) have rarely been investigated. A major challenge in a scalable technique is obtaining a uniform, highly crystalline, and ultrathin ETL at a low temperature. Here, large-area SnO2 ETLs are fabricated by an electrostatic self-assembly method. The ETLs coated onto haze FTO show high uniformity without pin holes, as confirmed by an electroluminescence image of the perovskite solar module (PSM). In addition, the uniform and pinhole-free SnO2 coating are indirectly verified by observing the unchanged shunt resistance of the PSC with increasing active area, compared to the conventional SnO2 ETL-based PSC. On the basis of this self-assembly method, PSMs of areas 25 and 100 cm(2) are fabricated with power conversion efficiencies (PCEs) of 15.3 and 14.0% without shunt resistance loss, respectively.
Keywords: EFFICIENT; CELLS; FILMS; DEPOSITION; LAYER; SCALE